IZOGLOSSA («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
This article provides information about the concept of isoglossa and its application. Isoglosses are complete (if the phenomenon is used in a certain region and does not occur outside of it), ring (if it occurs in different regions that are disconnected from each other), closed (if it does not occur anywhere but a certain limited area), open (if it occurs in different regions) it is shown that it can be.
Keywords: Descriptive dialectology, taxonomy, landscape, isoglossa, isoline, isomorpheme, isophoneme, isolexeme.